2006
DOI: 10.1097/01.iop.0000192649.23508.f7
|View full text |Cite
|
Sign up to set email alerts
|

Longitudinal Correlation of Thyroid-Stimulating Immunoglobulin With Clinical Activity of Disease in Thyroid-Associated Orbitopathy

Abstract: It was found that changes in inflammatory phase of TAO, as measured by the TAOS score, statistically correlate with changes in measured TSI. An additional correlation was also found between the absolute score of TAO activity and measured level of TSI. These findings suggest that serial TSI measurements may be an adjunct in assessing clinical inflammatory activity of TAO and may help direct clinical decision making regarding treatment decisions in TAO.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
30
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 41 publications
(33 citation statements)
references
References 43 publications
(34 reference statements)
3
30
0
Order By: Relevance
“…Specifically, several groups have found an association between TSI levels and the incidence of TAO. 1416 Our study supports the notion that a greater proportion of patients with TAO exhibit high TSI levels.…”
Section: Commentsupporting
confidence: 86%
“…Specifically, several groups have found an association between TSI levels and the incidence of TAO. 1416 Our study supports the notion that a greater proportion of patients with TAO exhibit high TSI levels.…”
Section: Commentsupporting
confidence: 86%
“…6,8,11,12 The TSI bioassay measures cyclic adenosine monophosphate production after TSAb binds to TSH receptor. [13][14][15] Thus, this method enables the identification of the functional characteristics of TRAb. With the development of the Mc4-CHO cell line, the cell culture protocols of the TRAb bioassays were simplified.…”
Section: Introductionmentioning
confidence: 99%
“…TBII titers and TSI concentrations are related to the development and deterioration of GO. Examination of the relationship between GO myopathy and the TSH receptor revealed that as the TRAb level increases, EOM enlargement and limitation also increases [19][20][21][22]. Resensburg et al reported that high TBII titers are associated with an increase in muscle volume and Jang et al reported that TSI concentration is associated with EOM limitation [16,23].…”
Section: Discussionmentioning
confidence: 98%